Pengelolaan Masjid Dalam Meningkatkan Aktivitas Keagamaan Di Masjid Nurul Iman Desa Sei Sentosa Labuhanbatu - Triadi, Muhammad Triadi; Ritonga, Kamaluddin; Hasibuan, Hasbi Anshori; Handayani, Ricka (Tadbir: Jurnal Manajemen Dakwah, 2024)
This research found that the management of the Masjid Nurul Iman in Desa Sei Sentosa, Labuhanbatu District, has more active religious activities compared to its previous state. This study was conducted using a qualitative descriptive approach aimed at objectively describing the actual situation in the field. The research used primary and secondary data. Primary data were obtained from three individuals from Masjid Nurul Iman’s management, namely the chairman, secretary, and treasurer. Meanwhile, secondary data were obtained from two religious figures, two local government officials, and three mosque congregants. Data collection instruments included structured interviews, non-participatory observation, and some field documentation. The results showed that the management of Masjid Nurul Iman is focused on enhancing religious activities, including the five daily prayers, Friday prayers, distribution of zakat fithrah, tarawih prayers, the slaughtering and distribution of qurban meat, solar and lunar eclipse prayers, tabliqh akbar, religious lectures, funeral prayers, the return of Hajj pilgrims, MTQ events, and torchlight processions. This indicates that the mosque’s management has been effective in the areas of Idarah, imarah, and riâ€™ayah.